The Social Effects of Culture - A Literature Review - Jeannotte, M. Sharon (Université d'Ottawa | University of Ottawa, 2017)
This literature review is intended as a background document on recent research on the social effects of culture. In it, the field of culture has been defined to include both the professional and amateur creative arts (visual, literary and performing), the industries and organizations that support them (broadcasting, film, publishing, sound recording, and digital media), and the curation and preservation activities that are often grouped under the label of “heritage” (museums, historic sites, archives, and libraries). The social field has been broadly surveyed and has included academic literature from across the various disciplines that normally constitute the “social” in modern societies, including health, education, social services, poverty reduction and social inclusion, aspects of the justice system , identity studies, and urban studies.
Keywords: Culture; Sustainability; Social cohesion; Inclusion; Wellbeing; Social capital